Redefine statistical significance. (January 2018) - Benjamin, Daniel; Berger, James; Johannesson, Magnus; Nosek, Brian; Wagenmakers, E.-J.; Berk, Richard; Bollen, Kenneth; Brembs, Björn; Brown, Lawrence; Camerer, Colin; Cesarini, David; Chambers, Christopher; et al.
We propose to change the defaultP -value threshold for statistical significance from 0.05 to 0.005 for claims of new discoveries.